2022
DOI: 10.1002/ldr.4514
|View full text |Cite
|
Sign up to set email alerts
|

Net primary productivity changes associated with landslides induced by the 2008 Wenchuan Earthquake

Abstract: The 2008 Wenchuan Earthquake triggered massive landslide erosion, especially in mountainous terrain, which had a great impact on carbon storage of the local terrestrial ecosystem. However, variation in carbon flux and restoration of ecosystem function after the Wenchuan Earthquake remain open issues. In this study, we evaluated the current restored vegetation productive capability on the coseismic landslide scars through moderate resolution imaging spectroradiometer (MODIS) net primary productivity (NPP) image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 98 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…These landslide-related disturbances (e.g., earthquaketriggered mass movements) impact plant communities directly, causing damage to plant biomass by either killing entire plants or removing parts of them, which is particularly severe within faulting zones [22]. Previous studies have shown that earthquake-induced landslides within active fault zones have led to significant losses in local vegetation net primary productivity [52,53]. In comparison to higher elevations, bedrock in lower-elevation slopes within fault zones undergoes more pronounced physical and chemical weathering [54].…”
Section: Elevation-dependent Contrasting Effects Of Fault Distributio...mentioning
confidence: 99%
“…These landslide-related disturbances (e.g., earthquaketriggered mass movements) impact plant communities directly, causing damage to plant biomass by either killing entire plants or removing parts of them, which is particularly severe within faulting zones [22]. Previous studies have shown that earthquake-induced landslides within active fault zones have led to significant losses in local vegetation net primary productivity [52,53]. In comparison to higher elevations, bedrock in lower-elevation slopes within fault zones undergoes more pronounced physical and chemical weathering [54].…”
Section: Elevation-dependent Contrasting Effects Of Fault Distributio...mentioning
confidence: 99%